Employing the Childlike Form in Salma Al-Alaq's Drawings - Mahmood, Awan Yousif (Journal of Tikrit University for Humanities, 2024)
The initial twenty years of the 21st. century were a significant era characterized by the emergence of new societal dynamics, advancements in modern technology, and diverse intellectual landscapes. This period also witnessed the rise of the Iraqi formation movement, with particular emphasis on the empowerment of Iraqi women. Additionally, artists explored various themes inspired by the prevailing circumstances affecting all segments of society, with a particular focus on the experiences of children. These creative endeavours were driven by a combination of external pressures and internal sources of inspiration. These artists engage in introspection of their artistic preoccupations in order to explore themes by employing forms that align with their content. Their objective is to utilize the childlike form as a means to convey a purpose and emphasize the significance of childhood. This particular category has captured the attention of Iraqi artists both within and outside the country, necessitating further exploration. This study examines the utilization of childlike elements in the artistic practices of contemporary female painters in Iraq. It focuses on Salma Al-Alaq’s works and it explores the connection between childhood themes and their associated forms, concepts, and sentimental connotations. This artistic phenomenon diverges significantly from the deliberate approach commonly observed in the works of male artists within the contemporary Iraqi art scene. Furthermore, it highlights how Iraqi feminist experiences have prompted a reevaluation of childlike forms from a distinct perspective, characterized by varying visions, methodologies, references, ideas, and interactions employed by contemporary feminist painters. The present study is confronted with a research challenge that has emerged from the following inquiry: In Salma Al-Allaq's drawings, is the use of the juvenile form explored.?